KAJIAN TERHADAP PENGARUH POTENSI PAJAK DAERAH DENGAN DITERAPKANNYA UNDANG-UNDANG NOMOR 28 TAHUN 2009 DI KABUPATEN SINTANG (Studi Kasus PBB Sektor Perkotaan di Kec. SIntang) - B61108023, CHRISTIANA LISANA NUNINGSIH (Jurnal Ekonomi Daerah (JEDA), 2016)
According to Budget in Sintang District, the revenue contribution is relatively small share of total revenue. During fical year 2006 to fiscal year 2010 thecontribution of an average local revenue to total revenue is only 4.02%. This small contribution of revenue shows an urgently needed to increase the potential of ;oca; revenue, either by intensification or extensification local revenue sources. The opportunities to increase local revenue is becoming greater with the application of law no. 28, 2009 on Regional Taxes and Retributions. In the Law No.28, 2009, there were expanding local tax objects, one of which is the transfer of land and building tax of Rural and Urban Sectors which was originally a part to the central tax into local tax. The target of annually income tax information letter in Sintang Regency increases from 2006 to 2007 at average 4.5%. It shows a possible increasing in the potential land building tax of Urban Sectors in the future. Another factor that greatly affects economic growth in Sintang is also increasing. In 2006 to 2009 economic growth in Sintang reached 5.02%, with the growth of the construction sectoraverage of 6.09%. it is expected by the number of residents increased revenue and better economic development, the land building tax of Urban Sectors can make a significant contribution in increasing the revenue. After conducting the research and processing the data with the assumption data from the land and building tax of Urban Sectors in 2010 and the assumption rates of urban sector at 0.11%, the average rate before the change in the law onregional taxes and retributions is Rp. 38.262,93, while the calculations based on Law Number 28, 2009 on average values obtained the land and building tax of Urban Sectors for the District of Sintang is Rp. 42,089.23. Thus the value of the land and building tax of Urban Sectors based on Law number 28, 2009 showed 10% higher than before the implemention of the changing of tax law. Keywords : Potential, Revenue, Land and Buildings Tax on Urban Sector.